ANGKA KUMAN PADA GAGANG PINTU FASILITAS PELAYANAN KESEHATAN DI WILAYAH SAMARINDA SEBERANG - Palandrai, Desy Natha Auliah Putri; Lamri; Dita Irianti Rukmana (Jurnal Analis Laboratorium Medik, 2023)
Health service facilities are places where health services are carried out promotively, preventively and become one of the places where diseases and infections spread. The spread of disease infection through germs on door handles which are objects that are very often used every day and have the potential to be a source of spread of germs from one person to another. This study aims to determine the number of germs on the doorknobs of health care facilities in the opposite Samarinda area. This type of research is descriptive which describes the results of the total germ number on the door handle, with the number of door handle swab samples in this study 27 samples, each of which is divided into 9 samples by testing using the Total Plate Number method with Plate Count Agar media then incubated 1 x 24 hours. The results of this study can be concluded that 63% meet quality standards with a value of less than 10 CFU / cm2 and 37% do not meet standards that exceed the number of quality standards more than 10 CFU / cm2.